Governmentality and somatocracy in the Regime of Explicit Health Guarantees in Chile - Castillo-Sepúlveda, Jorge (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
Among the different technologies of neoliberal government emerging during the XX and XXI centuries, those that have attracted greater attention and reflection probably refer to those related to the processes of life, and the conception of it as a field for politics. This paper addresses the neoliberal governmental rationality involved in the development of the last major health reform in Chile: the Regime of Explicit Health Guarantees (GES), considering the implications of their epistemic aspects in understanding of corporeality. We consider as material for analysis several accounts of experts who have participated in the design of the regime, professionals involved in its implementation, legal and technical documents, and ethnographic observations. We analyse such information considering the notion of enactment proposed by Annemarie Mol. Results expose the processes of epistemic ordering, biopolitical acceleration, and biocitizenship prescription, linked to the enactment of the body as an assemblage of different spaces of government. We call such process as somatocracy, using the notion created by Michel Foucault. We conclude by integrating some components to think biocitizenship from emerging aspects in the work.